Risk Management in Construction Firms in Nepal - Sukamani, Umesh (Journal of Science and Engineering, 2021)
The main purpose of this study is to identify and focus on major factors that affect risk management in construction sites in developing countries like Nepal. Relative Importance Index (RII) analysis is carried out to rank major factors that affect risk management. Besides, ANOVA analysis is carried out to test the hypothesis. Findings show that there is no difference between small and large-scale project groups in their perception of the significance level of factors affecting Project Risk Management. Moreover, “a) payment delay b) project funding problem, and c) defective design” were top three major factors that affect risk management in developing countries like Nepal. The managerial level of construction firms mainly in developing countries, should focus on the top ten critical factors for better improvement of risk management no matter its size- be it is small- or large scale construction firms.